Large Complex Odontoma of Mandible in a Young Boy: A Rare and Unusual Case Report - G. Siva Prasad Reddy; G. V. Reddy; B. Sidhartha; K. Sriharsha; John Koshy; Rehana Sultana (Case Reports in Dentistry)
Odontomas are the most common odontogenic tumors. They are broadly classified in to Compound Odontoma and Complex Odontoma. Among them complex odontoma is a rare tumor. Occasionally this tumor becomes large, causing expansion of bone followed by facial asymmetry. Otherwise these tumors are asymptomatic and are generally diagnosed on radiographic examination. We report a rare case of complex odontoma of mandible in a young boy. The tumor was treated by surgical excision under general anesthesia.